COMPARISON OF SOIL-TRANSMITTED HELMINTH EGG INFESTATION IN FECES OF INTELLECTUAL DISABILITY (ID) CHILDREN WITH NON-ID CHILDREN - Mellyna Iriyanti Sujana; Amanah Amanah; Moch Yusuf Handoyo (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The worm infestation is considered as one of the causes of cognitive function disruption. It also can aggravate the condition in children with intellectual disability (ID). This greatly affects health conditions, such as abdominal pain, bloating, diarrhoea, constipation and other digestive disorders. Indigestion may increase aggressive behaviour, mood change and malnutrition so that it leads to chronic malnutrition which is the cause of major morbidity and premature death in the ID population. This study aimed to compare soil-transmitted helminth egg infestation in stool samples between ID children and non-ID children. Methodology: This present study was a descriptive study with a cross sectional design. Stool samples was collected from 30 students from Special Need School and 60 students from Elementary School in the Cirebon City. The floating method was used to identify the egg of soil-transmitted helminth. The stool samples were examined in the Laboratory of the Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia Results: The laboratory test found positively Soil-transmitted Helminth eggs in 9 of 30 stool sample of ID students. Among them, it was found 5 stool samples with Ascaris lumbricoides, 2 stool samples of Trichuris trichiura, and 2 stool samples of Necator americanus. Regarding their levels, 4 students (44.4%) had mild intellectual disability and 5 students (55.6%) had moderate intellectual disability. However, there was not found any Soil-transmitted Helminth eggs in stool samples of non-ID children. Conclusion: Soil-transmitted helminth eggs was found only in stool samples of ID children. The hygiene and sanitation in the school should be guaranteed to prevent the transmission of Soil-transmitted Helminth. Key words: Soil-Transmitted Helminth, Intellectual Disability (ID), Feces